Monkeypox: a rising threat - Sadia Choudhury Shimmi (Penerbit UMS, 2024)
Monkeypox (mpox) has recently emerged as a global health emergency. This zoonotic disease is caused by the monkeypox virus (MPXV), an enveloped double-stranded DNA virus belonging to the Orthopoxvirus genus in the Poxviridae family, which also includes viruses such as variola (smallpox), cowpox, and vaccinia. The monkeypox virus is part of the same family as the virus that causes smallpox.